The Personnel Administration of the Education Section of Pattani Primary Educational Service Area Office 2 - Hama, Wasueman (Al-HIKMAH Journal, 2022)
This study included the purpose (1) to study the personnel management level of school administrators under the Pattani Elementary School District 2 (2) to compare the level of personnel management of school administrators under the Pattani Elementary School District 2, classified by gender, education level, work experience, and school size, (3) to process issues and personnel management recommendations of school administrators under Pattani elementary school district 2. The sample was 331 teachers affiliated with Pattani elementary school district 2. Analyze data using ready-made programs and statistics used: average, percentage, standard deviation. t-test and F-test The research found that The personnel management level of school administrators under Pattani elementary school office District 2 overall is at a high level. The results of comparative personnel management of school administrators under Pattani elementary school district office District 2, classified by gender, work experience and school size, found that the overall and each aspect were not different, and teachers with different levels of education were found to be different. There were no differences in opinions on personnel management of school administrators overall, but considering individual aspects, there was a statistically significant difference in opinions on personnel management of school administrators at .05. The suggestions of school administrators under Pattani elementary school district 2, school administrators should have needle-tested personnel in order to get people into the workforce effectively. Operational experiments should be conducted, personnel should be developed regularly. Schools should provide training to teachers and modern teaching processes. Personnel should be asked to study from other successful agencies. Administrators must be fair, should establish a committee to evaluate, should prioritize all staff in the school as morale in the performance of duties, and should set clear standards of rules for salary promotion. Salary promotions must be clear and verifiable. There should be clear assessment rules. This makes the personnel more apprehensive in their duties. The service provider should be monitored and admonished if the teacher is found guilt